HUBUNGAN KONTROL DIRI DAN KONFORMITAS TEMAN SEBAYA TERHADAP PERILAKU KONSUMTIF SISWA MAN 1 MOJOKERTO - Madina, Tasya Nur; Nastiti, Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
A person's desire to purchase goods or services impulsively and without reason is known as consumptive behavior. This behavior is usually driven by the need for pleasure and social recognition. The purpose of this study was to investigate how consumer behavior in students of MAN 1 Mojokerto is associated with self-control and peer acceptance. The correlational method was used, and product moment statistical analysis was used. The study involved 243 students from grades 10 and 11 selected using a probability sampling method with a 5% error significance level. The scales used included consumptive behavior, self-control, and peer conformity scales. The results showed that there was a positive and significant relationship between consumptive behavior, self-control, and peer conformity in students of MAN 1 Mojokerto. This finding confirms that low Self-Control accompanied by high Peer Conformity increases the tendency for Consumptive Behavior.